Azole resistance in Aspergillus fumigatus from bronchoalveolar lavage fluid samples of patients with chronic diseases - Zhao, Yanan (Oxford University Press, 2013)
OBJECTIVES: Triazole resistance in Aspergillus fumigatus has been increasing. We explored the A. fumigatus azole resistance profiles in bronchoalveolar lavage (BAL) fluid samples from Danish patients examined for aspergillosis. METHODS: A total of 94 BAL samples from 87 patients were evaluated by galactomannan (GM) test and A. fumigatus CYP51A profiling by PCR. RESULTS: Aspergillus spp. were isolated from 27/48 (56.3%) cultured samples, including 23 A. fumigatus with one resistant strain (4.3%). Samples were classified into GM-positive (≥3.0), GM-intermediate (0.5 to <3.0) and GM-negative (<0.5) groups, where the CYP51A PCR was positive in 81.8% (36/44), 56.3% (18/32) and 38.9% (7/18) of samples, respectively. Nine CYP51A PCR-positive samples (9/61, 14.8%) were found to have mutations resulting in amino acid substitutions. M220V was detected from a sample culture positive for susceptible A. fumigatus and P216L was found in a culture-negative BAL sample. Conversely, no mutation was found in one sample culture positive for azole-resistant A. fumigatus. The tandem repeat/L98H mutation was not detected. CONCLUSIONS: Our study shows that azole resistance in A. fumigatus can be cryptic and may go undiagnosed. The combination of improved culture/susceptibility tests and the direct molecular detection of resistance markers will facilitate prompt institution of appropriate antifungal therapy.